EFFECT CAMA- RAYS OF PHYSICSL PROPERTIES TO SAME ISOLATES - WALEED BEDEAWY SALIH; JASSIM MAHAMMED SALIH (مجلة جامعة الانبار للعلوم الصرفة, 2009)
The effect of γ–rays from CO60 at different doses (2000,3000,4000 rad) to the pure unsaturated polyester. Have been studied though the electric properties: impedance, dielectric constant, loss factor and a.|c. conductivity. The effects of γ- radiation of different doses increased the impedance and decreases the dielectric constant loss factor and the a.c. conductivity due to the degradation process